Airway management in out-of-hospital cardiac arrest: A systematic review and network meta-analysis - Lou, Jing; Tian, Sijia; Kang, Xuqin; Lian, Huixin; Liu, Hongmei; Zhang, Wenzhong; Peran, David; Zhang, Jinjun (The American journal of emergency medicine, 2023)
OBJECTIVES: Airway management during cardiopulmonary resuscitation is particularly important for patients with out-of-hospital cardiac arrest (OHCA). This study was performed to compare the efficacy of the most commonly used out-of-hospital airway management methods in increasing the survival to discharge in patients with OHCA. METHODS: We screened all relevant literature from database inception to 21st January 2019 in PubMed, Web of Science, Embase, and the Cochrane Library. We included all randomized controlled trials (RCTs) of airway management for OHCA in adults (≥16 years of age) with no limitations on publication status, publication date, or language. The primary outcome was survival to discharge. The secondary outcomes were the overall airway technique success rate, return of spontaneous circulation, and survival to hospital admission. RESULTS: Overall, from 1986 to 2018, 9 RCTs involving 13,949 patients were included in the network meta-analysis, and the efficacy of six airway management methods for patients with OHCA were compared. However, none of the results were statistically significant. CONCLUSIONS: As the gold standard of airway management for patients with out-of-hospital cardiac arrest in most countries, endotracheal intubation (ETI) has been widely used for many years. However, our systematic review and network meta-analysis showed that ETI is no better than other methods in increasing the survival to discharge. This is not directly proportional to the various preparations required before ETI. Additional randomized controlled trials are needed to identify more effective methods and improve patients' outcome.
Keywords: Airway Management; Network meta-analysis; intratracheální intubace; urgentní zdravotnické služby; zástava srdce mimo nemocnici; Out-of-Hospital Cardiac Arrest; Adult; dospělí; zajištění dýchacích cest; Intubation, Intratracheal; Humans; lidé; kardiopulmonální resuscitace; Cardiac arrest; Out-of-hospital; Cardiopulmonary Resuscitation; Airway management; Emergency Medical Services